Przebieg prac nad przygotowaniem projektów kodyfikacji karnej z 1997 roku, ze szczególnym uwzględnieniem projektu kodeksu karnego wykonawczego - Lelental, Stefan; Niewiadomska-Krawczyk, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The study focuses on attempting to reproduce works on the applicable executive penal code. The act adopted in 1997 was created in the course of many years of discus-sion of an entire team of the most outstanding specialists. The study contains comments on detailed solutions and their modifications in the course of the Code. The authors point out the further need to improve the adopted solutions regarding the execution of penalties.
Keywords: Komisja Kodyfikacyjna; kodeks karny wykonawczy; zwolnienie warunkowe